Novel approaches to management of hypertension - Bosch, Agnes; Schmieder, Roland (Current Opinion in Nephrology and Hypertension, 2021)
Purpose of review Of the roughly 1.4 billion people with hypertension worldwide, only about one in seven has their blood pressure (BP) successfully treated and adequately controlled. This review will focus on new therapeutic approaches of hypertension. Recent findings Several recent clinical studies and guidelines have favoured the assessment of target organ damage and cardiovascular risk scores for the diagnosis and treatment approach of hypertension. Paradigm shifts recommended in the guidelines are the initiation of antihypertensive treatment with combination (not mono) therapy and the recommendation of single-pill combinations (SPC), which improve adherence and result in rapid and effective BP control. In clinical trials with optimized design and renal denervation (RDN) technology, the biological proof of concept has been established. Consistent, durable ambulatory and office BP reductions without procedure associated serious adverse events have been documented. The challenges are now to identify patients who respond best to interventional treatment. Major key points in the treatment strategy for hypertension are: individualization of the therapy according to total cardiovascular risk, combination therapy as initial step, recommendation of SPC and RDN as promising interventional therapy.
CRIS-Team WoS Importer:2021-01-15